PENERAPAN PENGENDALIAN INTERN TERHADAP PEMBERIAN KREDIT PADA KSP LOHJINAWE CABANG PEMBANTU KUNDURANKANTOR CABANG BLORA - Joti Dina Kartikasari; Nikmatuniayah Nikmatuniayah; Muhammad Asrori (Politeknik Negeri Semarang, 2021)
This research aims to implement an understanding of internal control and internal control components in KSP Lohjinawe Cabang Pembantu Kunduran Kantor Cabang Blora with internal control components which include the control environment, risk assessment, control activities, information and communication, and monitoring. The application of internal control in KSP Lohjinawe Cabang Pembantu Kunduran Kantor Cabang Blora uses data obtained through interviews, questionnaires, literature studies, and observations. From the results of the analysis it can be concluded that the understanding of internal control has been running well documented with the internal control questionnaire, flowchart, and the narrative and internal control components that have been implemented have been running well, the cooperative establishes various control activities for the risk of non-performing loans that arise.